(untitled) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the pedagogical significance of developing reflexive skills in primary school students and the effective methods used to implement this process. The article discusses how the reflexive process impacts the success of students by helping them evaluate their actions, analyze the learning process, and identify their shortcomings. It highlights the methods employed by teachers to develop independent thinking, self-awareness, and effective learning, including group work, keeping reflective journals, and interactive exercises. The research findings confirm the crucial role of developing reflexive skills in improving the efficiency of the learning process.